Factors Influencing Impulse Buying Behavior among Working Ladies in Selangor, Malaysia - Chan Yuen Yue; Abd Razak, Ahmad Zainal Abidin (International Business Education Journal, 2022)
The objective of this research is to determine the effect of extrinsic cues on impulse buying behavior amongst working ladies. The extrinsic cues are measured based on price, store atmosphere, brand reputation, country of origin and social influence. 400 full-time working ladies aged between 16 to 35 years old, who are selected based on purposive sampling technique, are surveyed at One Utama shopping mall, Selangor. The data collected are then analyzed using SPSS (Statistical Packages for the Social Science). The findings revealed that price (β = -0.407, p < 0.05), store atmosphere (β = 0.359, p < 0.05) and social influence (β = -0.331, p < 0.05) significantly influence impulse buying behavior of working ladies. However, brand reputation (β = -0.170, p > 0.05) and country of origin (β = -0.106, p > 0.05) of the product do not significantly influence impulse buying behavior of working ladies. In conclusion, this research provides useful information and insight to the marketers about the working ladies market segment. Accordingly, marketers should prepare their marketing strategies based on price, store atmosphere and social influence to attract more working ladies.